THE EFFICIENCY ANALYSIS OF SHARIA LIFE INSURANCE IN INDONESIA AND FAMILY TAKAFUL IN MALAYSIA USING DATA ENVELOPMENT ANALYSIS METHOD (CASE STUDY ON AL ABRAR'S SHARIAH FINANCIAL SERVICE COOPERATIVE) - Muhammad Iqbal Rifqi Ardianto; Puji Sucia Sukmaningrum (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aims to determine the level of efficiency of Sharia life insurance in Indonesia and Malaysia during the 2015-2018 period. The sample used was 12 Sharia life insurance companies in Indonesia and 5 Sharia life insurance companies in Malaysia. The method used in this research is Data Envelopment Analysis (DEA) with the assumption of Variable Return to Scale (VRS) with input-orientation. The selection of variables uses a value-added approach with its input variables, namely capital, total expenses, and total investment as well as its output variables, namely total profit and total investment income. The results of this study indicate that the average overall value of sharia life insurance efficiency in Indonesia is relatively lower than the average efficiency of sharia life insurance in Malaysia. The development trend of the efficiency of Sharia life insurance in Indonesia and Malaysia tends to decrease during 2015-2018. Meanwhile, the cause of inefficiency in Sharia life insurance in Indonesia and Malaysia is the total expenses variable. Keywords: Efficiency, Sharia Life Insurance, DEAREFFERENCE Akhtar, M. H. (2017). Performance analysis of takaful and conventional insurance companies in Saudi Arabia. Benchmarking: An International Journal, 25(30), 00-00. https://doi.org/10.1108/BIJ-01-2017-0018Antonio, M. S., Ali, M. M., & Nashr. (2013). A comparative analysis of the efficiency of takaful and conventional insurance in Malaysia. International Journal of Excellence in Islamic Banking and Finance, 3(1), 1-13.Astuti, Y. F., & Suprayogi, N. (2017). Perbedaan efisiensi perusahaan asuransi jiwa syariah dan konvensional di Indonesia dengan metode data envelopment analysis (DEA). Jurnal Ekonomi Syariah Teori dan Terapan, 4(8), 668-683.DIEDC. (2018). An inclusive ethical economy: state of the global Islamic economy report 2018/19. Dubai: Dubai the Capital of Islamic Economy.Faruk, M. O., & Rahaman, A. (2015). Measuring efficiency of conventional life insurance companies in Bangladesh and takaful life insurance companies in Malaysia:  A non-parametric approach. Management Studies and Economic Systems, 2(2), 129-144.IFSB. (2018). Islamic Financial Services Industry Stability Report 2018. Kuala      Lumpur: Islamic Financial Services Board.IFSB. (2019). Islamic Financial Services Industry Stability Report 2019. Kuala      Lumpur: Islamic Financial Services Board.Miniaoui, H., & Chaibi, A. (2014). Technical efficiency of takaful industry: a comparative study of Malaysia and GCC countries (Working Paper). IPAG Business School.MTA. (2018). Malaysian Takaful Annual Report 2018. Kuala Lumpur: Malaysian Takaful Associaton.MUI. (2014). Himpunan Fatwa Keuangan Syariah Dewan Syariah Nasional MUI. Jakarta: Penerbit Erlangga.Ningsih, Y. W., & Suprayogi, N. (2017). Analisis efisiensi asuransi umum Syariah di Indonesia tahun 2013-2015: Aplikasi metode data envelopment analysis. Jurnal Ekonomi Syariah Teori dan Terapan, 4(9), 575-772.Nurdiansyah, M. F. (2019). Analisis efisiensi perusahaan asuransi syariah di Indonesia periode 2014-2017 dengan metode Data Envelopment Analysis. Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Rusydiana, A. S., & Tim Smart Consulting. (2013). Mengukur tingkat efisiensi dengan data envelopment analysis (DEA): Teori dan aplikasi. Bogor: SMART Publishing.Saad, N. M., & Idris, N. E. H. (2011). Efficiency of life insurance companies in Malaysia and Brunei: A comparative analysis. International Journal of Humanities and Social Science, 1(3), 111-122.Sabiti, M. B., Effendi, J., & Novianti, T. (2017). Efisiensi asuransi syariah di Indonesia dengan pendekatan data envelopment analysis. Jurnal Al-Muzara’ah,5(1), 69-87.Sholihin, A. I. (2010). Buku Pintar Ekonomi Syariah. Jakarta: GramediaTuffahati, H., Mardian, S., & Suprapto, E. (2016). Pengukuran efisiensi asuransi syariah dengan data envelopment analysis (DEA). Jurnal Akuntansi dan Keuangan Islam, 4(1), 1-23. Thomson Reuters. (2018). Islamic Finance Development Report 2018, Buliding Momentum: Thomson Reuters.